2017
DOI: 10.4236/as.2017.83015
|View full text |Cite
|
Sign up to set email alerts
|

Agriculture, Profitability and Climate Change: Can Accounting Help Identify Best Farming Practices? Empirical Case Study in Spain

Abstract: We perform an empirical analysis on the benefits of, and the challenges faced by, sustainability accounting in measuring the effects of climate change for a sample of Spanish rice farms. We use farm yields, revenues and incomes as indicators of economic performance, and greenhouse gas emissions, and direct and indirect energy consumption as indicators of climate change effects. According to our data, farms with higher yields, revenues and income are responsible for a greater environmental impact, measured in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…It is known that accounting can support organisational climate change adaptation by performing the following functions: a risk assessment function, a valuation function and a disclosure function (Linnenluecke et al , 2015). Hence, concentration on financially informed tools could provide better information on farmers’ natural and economic risks and opportunities (Bremer and Linnenluecke, 2017; Antonini and Argilés Bosch, 2017). But accounting systems can also provide an opportunity for improved business knowledge and skills, improved farm valuation awareness and communication with key stakeholders, especially when integrated with smart technologies (Mancini et al , 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that accounting can support organisational climate change adaptation by performing the following functions: a risk assessment function, a valuation function and a disclosure function (Linnenluecke et al , 2015). Hence, concentration on financially informed tools could provide better information on farmers’ natural and economic risks and opportunities (Bremer and Linnenluecke, 2017; Antonini and Argilés Bosch, 2017). But accounting systems can also provide an opportunity for improved business knowledge and skills, improved farm valuation awareness and communication with key stakeholders, especially when integrated with smart technologies (Mancini et al , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Such decision-making tools include improved accounting and finance methods and information that can support awareness and increase profitability (Mancini et al , 2021), but can also mean a better understanding of natural resource use and improved environmental outcomes (Ogilvy et al , 2018; Tingey-Holyoak et al , 2019, 2020, 2021a). Recent research has shown that improved access to relevant accounting information can also build adaptive capacity to climate change impacts (Antonini and Argilés Bosch, 2017). Whilst interest is growing around farm accounting and resulting benefits in farm productivity and efficiency, there is still a need for more robust accounting innovations to further support farmer decision-making (Argilés and Slof, 2003; Jack, 2005, 2006; Jakobsen, 2017; Ndemewah et al , 2019; Gottlieb et al , 2021).…”
Section: Introductionmentioning
confidence: 99%